Spironolactone Treatment and Effect on Survival in Chronic Heart Failure Patients with Reduced Renal Function: A Propensity-Matched Study - Stubnova, Viera (Cardiorenal Med, 2017)
BACKGROUND/AIMS: Spironolactone may be hazardous in heart failure (HF) patients with renal dysfunction due to risk of hyperkalemia and worsened renal function. We aimed to evaluate the effect of spironolactone on all-cause mortality in HF outpatients with renal dysfunction in a propensity-score-matched study. METHODS: A total of 2,077 patients from the Norwegian Heart Failure Registry with renal dysfunction (eGFR <60 mL/min/1.73 m(2)) not treated with spironolactone at the first visit at the HF clinic were eligible for the study. Patients started on spironolactone at the outpatient HF clinics (n = 206) were propensity-score-matched 1:1 with patients not started on spironolactone, based on 16 measured baseline characteristics. Kaplan-Meier and Cox regression analyses were used to investigate the independent effect of spironolactone on 2-year all-cause mortality. RESULTS: Propensity score matching identified 170 pairs of patients, one group receiving spironolactone and the other not. The two groups were well matched (mean age 76.7 ± 8.1 years, 66.4% males, and eGFR 46.2 ± 10.2 mL/min/1.73 m(2)). Treatment with spironolactone was associated with increased potassium (delta potassium 0.31 ± 0.55 vs. 0.05 ± 0.41 mmol/L, p < 0.001) and decreased eGFR (delta eGFR −4.12 ± 12.2 vs. −0.98 ± 7.88 mL/min/1.73 m(2), p = 0.006) compared to the non-spironolactone group. After 2 years, 84% of patients were alive in the spironolactone group and 73% of patients in the non-spironolactone group (HR 0.59, 95% CI 0.37-0.92, p = 0.020). CONCLUSION: In HF outpatients with renal dysfunction, treatment with spironolactone was associated with improved 2-year survival compared to well-matched patients not treated with spironolactone. Favorable survival was observed despite worsened renal function and increased potassium in the spironolactone group.